Involvement of sugar and abscisic acid in the genotype-specific response of rose to far-red light - Crespel, Laurent; Le Bras, Camille; Amoroso, Thomas; Dubuc, Bénédicte; Citerne, Sylvie; Perez-Garcia, Maria-Dolores; Sakr, Soulaiman (Frontiers in Plant Science, 2022)
Plant architecture determines yield (fruit or flowers) and product quality in many horticultural species. It results from growth and branching processes and is dependent on genetic and environmental factors such as light quality. Highly significant genotype and light quality effects and their interaction have been demonstrated on the architecture of rose. Far-red (FR) light is known for this favourable effect on plant growth and development. We evaluated the effect of FR on rose growth and development and its interaction with the genotype through architectural, eco-physiological (net photosynthesis rate) and biochemical (sugar and hormone concentrations) approaches. Two cultivars (‘The Fairy’ – TF – and Knock Out® Radrazz – KO) with contrasting architectures were grown in a climate chamber under FR or in the absence of FR at an average photosynthetic photon flux density (400-700 nm) of 181.7±12.8 µmol m-2 s-1 for 16h. A significant effect of FR on the architecture of TF was demonstrated, marked by greater stem elongation, shoot branching and flowering, while KO remained insensitive to FR, supporting a genotype x FR interaction. The response of TF to FR was associated with improved photosynthetic capabilities, while KO exhibited an elevated level of abscisic acid (ABA) in its leaves. FR-dependent ABA accumulation might inhibit photosynthesis and prevent the increased plant carbon status required for growth. From a practical perspective, these findings argue in favour of a better reasoning of the choice of the cultivars grown in lighted production systems. Further investigations will be necessary to better understand these genotype-specific responses to FR and to unravel their molecular determinants.